Pengaruh Customer Service dan Customer Experience Terhadap Minat Ulang Pembelian Pada Toko Greensmart (Studi Kasus Toko Greensmart Sepande Sidarjo) - Sholikhah, Afifatus; Eko Pujianto, Wahyu (Universitas Respati Indonesia, 2024)
The purpose of this study to examine the effect of customer service consists of number of consumers handled, level of customer satisfaction, speed of initial response and customer retention rate on customer experience consists of sense experience, feel experience, think experience, act experience and think experience towards re-interest in purchases at Greensmart Sepande Sidoarjo store. The research approach uses quantitative with questionnaires as a data collection tool. The sampling technique in this study used random sampling obtained by 100 respondents. The results of the study explained that customer service and customer experience have a very significant influence on the re-interest in purchases at the Greensmart Sepande Sidoarjo store.